Epithelial to Mesenchymal Transition in Patients with Pancreatic Ductal Adenocarcinoma: State-of-the-Art and Therapeutic Opportunities - Julie Dardare; Andréa Witz; Jean-Louis Merlin; Agathe Bochnakian; Paul Toussaint; Pauline Gilson; Alexandre Harlé (Pharmaceuticals, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is one of the malignancies with the worst prognosis despite a decade of efforts. Up to eighty percent of patients are managed at late stages with metastatic disease, in part due to a lack of diagnosis. The effectiveness of PDAC therapies is challenged by the early and widespread metastasis. Epithelial to mesenchymal transition (EMT) is a major driver of cancer progression and metastasis. This process allows cancer cells to gain invasive properties by switching their phenotype from epithelial to mesenchymal. The importance of EMT has been largely described in PDAC, and its importance is notably highlighted by the two major subtypes found in PDAC: the classical epithelial and the quasi-mesenchymal subtypes. Quasi-mesenchymal subtypes have been associated with a poorer prognosis. EMT has also been associated with resistance to treatments such as chemotherapy and immunotherapy. EMT is associated with several key molecular markers both epithelial and mesenchymal. Those markers might be helpful as a biomarker in PDAC diagnosis. EMT might becoming a key new target of interest for the treatment PDAC. In this review, we describe the role of EMT in PDAC, its contribution in diagnosis, in the orientation and treatment follow-up. We also discuss the putative role of EMT as a new therapeutic target in the management of PDAC.